2005
DOI: 10.1002/marc.200500598
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Morphology of Metallo‐Supramolecular Block Copolymers with Bulky Counter Ions

Abstract: Summary: The phase behavior of metallo‐supramolecular block copolymers with bulky counter ions is theoretically studied within the framework of a mean‐field dynamic density functional theory and compared with recent experiments on a polystyrene–poly(ethylene oxide) metallo‐supramolecular diblock copolymer, PS20‐[Ru]‐PEO70, with tetraphenylborate counter ions. The copolymer is modeled as a triblock polyelectrolyte, in which the metal complex is treated as the polyelectrolyte block. The topology and kinetics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…9 In addition, the properties of the metal complexes, such as electrochemical and photophysical properties, could provide additional features to the block copolymers4f,j, 8, 9c and may even lead to modification of the intrinsic properties of the polymers through their supramolecular chemistry, resulting in totally unique features that are not found in either the polymers or the metal complexes alone 8. 9d,e, 10a However, so far, only a few studies have reported the hybrid properties found in metallosupramolecular block copolymers, such as the effect of counter ions of the metal complexes on the nanostructure of the block copolymers 9d. 10a…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, the properties of the metal complexes, such as electrochemical and photophysical properties, could provide additional features to the block copolymers4f,j, 8, 9c and may even lead to modification of the intrinsic properties of the polymers through their supramolecular chemistry, resulting in totally unique features that are not found in either the polymers or the metal complexes alone 8. 9d,e, 10a However, so far, only a few studies have reported the hybrid properties found in metallosupramolecular block copolymers, such as the effect of counter ions of the metal complexes on the nanostructure of the block copolymers 9d. 10a…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, the properties of the metal complexes, such as electrochemical and photophysical properties, could provide additional features to the block copolymers4f,j, 8, 9c and may even lead to modification of the intrinsic properties of the polymers through their supramolecular chemistry, resulting in totally unique features that are not found in either the polymers or the metal complexes alone 8. 9d,e, 10a However, so far, only a few studies have reported the hybrid properties found in metallosupramolecular block copolymers, such as the effect of counter ions of the metal complexes on the nanostructure of the block copolymers 9d. 10a…”
Section: Introductionmentioning
confidence: 99%